2015
DOI: 10.14203/j.mev.2015.v6.113-122
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between Internal Ohmic Resistance and Capacity for Battery State of Health Estimation

Abstract: In order to avoid battery failure, a battery management system (BMS) is necessary. Battery state of charge (SOC) and state of health (SOH) are part of information provided by a BMS. This research analyzes methods to estimate SOH based lithium polymer battery on change of its internal resistance and its capacity. Recursive least square (RLS) algorithm was used to estimate internal ohmic resistance while coloumb counting was used to predict the change in the battery capacity. For the estimation algorithm, the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Differently from the approaches in the above references, SOH is a standard approach that uses some indirect estimations. It is possible to calculate SOH based on capacity or internal resistance [30,38,39]. Calculating the SOH based on capacity is a traditional mathematical approach that takes into account the entire accumulated discharge current for a cycle.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Differently from the approaches in the above references, SOH is a standard approach that uses some indirect estimations. It is possible to calculate SOH based on capacity or internal resistance [30,38,39]. Calculating the SOH based on capacity is a traditional mathematical approach that takes into account the entire accumulated discharge current for a cycle.…”
Section: State-of-the-artmentioning
confidence: 99%
“…As a result, only ions are allowed to pass between the electrodes when using this method. Thus, individual Li ions do not need to entirely drive from the anode to the cathode through the circuit [21]. The space between the electrodes is filled with liquid.…”
Section: Electrolytementioning
confidence: 99%
“…Estimation speed and reliability have been compared between internal ohmic resistance based estimation and capacity based estimation. It can be concluded that SOH estimation based on internal resistance is faster and more reliable [12].…”
Section: Introductionmentioning
confidence: 96%